Psychological Mechanisms of Decision-Making in Administrative Activity - Safarovich, Kurbanov Jaloliddin (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the organization of educational quality management activities and the professional development of the heads of various departments, directions, problems of improving their qualifications, detailed information on some aspects of the management activities of the heads of educational institutions and the problems of introducing strategic management in educational systems, as well as on the problems of developing the theoretical and methodological foundations of the management of educational systems and institutions.